Immunoregulatory impact of human mesenchymal-conditioned media and mesenchymal derived exosomes on monocytes - Tokhanbigli, Samaneh (Mol Biol Res Commun, 2019)
Mesenchymal stem cells (MSCs) are well known due to their immunomodulatory effect, but the exact mechanisms have not been defined. Several studies demonstrated that the exerted immunoregulatory effect of these cells could be mediated by paracrine factors to illustrate, cytokines, chemokine, and among which, extracellular vesicles are one of them to play a crucial role. Moreover, it is assumed that extracellular vesicles are an essential player in intracellular communication by transferring their component. In this respect, the efficiency of conditioned media and exosomes was compared to illustrate a practical approach to cell-free based therapies. In the current study, we investigated the effect of both MSCs conditioned media (MSC-CM) and MSCs-derived exosomes on the expression of pro-inflammatory and anti-inflammatory cytokines in peripheral blood mononuclear cells (PBMCs). In this regard, isolated PBMCs were treated with MSC-CM and MSC-derived exosome as separated groups. Expression of inflammatory and anti-inflammatory markers was evaluated by Real-time PCR and ELISA. The immunoregulatory effect of MSC-CM on pro-inflammatory and anti-inflammatory genes, such as IL-12b, iNOS, EGR-2, IL-10 with an exception in case of IL-6 was more significant. Whereas in protein levels IL-10 showed the most substantial difference in exosome treated groups. It could be assumed that MSC-CM has more immunoregulatory impact on monocyte in contrast with exosomes.Taken together, by considering the recent approaches to cell-free therapy and the immunoregulatory impact of MSCs, yet relatively little is known about the efficacy of human-MSC-CM and secreted exosome compared with each other.